Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If I have this $(3 \times 4 + 2)^2$,

How can I simplify it with out the final result.

Do I distribute the $^2$ over each number like this:

$(3^2 \times 4^2 + 2^2)$?

What is the rule?

share|improve this question
4  
Do you think $(1+2)^2=1^2+2^2$? –  Did Mar 12 '12 at 8:47
2  
The rule is $(a+b)^2 = a^2+2ab+b^2$ - but it is not clear, what do you mean by a simplification. You may consider to take $2$ out of brackets: $$ (3\cdot 4+2)^2 = 2^2(3\cdot 2+1)^2 = 4\cdot 7^2 = 196 $$ –  Ilya Mar 12 '12 at 8:49
1  
Why dont you simplify it first and then open the square, and get (12+2)^2 = 14^2 = 196 –  Tomarinator Mar 12 '12 at 9:34
3  
How did this got tagged under number theory I wonder. –  Tomarinator Mar 12 '12 at 11:23
add comment

5 Answers 5

up vote 1 down vote accepted

$(3 \times 4 + 2)^2 = (12 + 2)^2 = 14^2 =196$ while $(3^2 \times 4^2 + 2^2) = 9 \times 16 +4 = 144+4 = 148$, so that does not work.

If you want a rule for squares of sums, try: $$(x+y)^2 = x^2 + 2 x y +y^2.$$

share|improve this answer
    
I want a rule for $(2s + 1)^2$, too –  Franceia Mar 12 '12 at 8:58
1  
From $(x+y)^2 = x^2 + 2 x y +y^2$, let $x=2s$ and $y=1$ to get $(2s)^2+2\times 2s \times 1 + (1)^2$ which you can easily tidy up. Note that $(2s)^2 = 2^2 \times s^2$. –  Henry Mar 12 '12 at 9:04
add comment

Always go basic by using the order of operations:

  • Parentheses.
  • Exponents.
  • Multiplication and division.(left to right)
  • Subtraction and addition.(no same order)

Using the PEMDAS rule, first simplify the parentheses, then simplify the exponent(s). We have,$$ 3 \times 4 + 2$$in the parentheses. Notice that again, PEMDAS is applied. Multiplication is done before addition. So, the simplification of the parentheses is as follows. $$\begin{align}3 \times 4 + 2 & = \color{maroon}{3 \times 4} + 2 \\ & = 12 + 2 \\ & = 14 \end{align}$$Now, the exponent. We'd have everything simplified as shown below: $$\begin{align} (3 \times 4 + 2)^2 & = & 14^2 \\ & = & 14 \times 14 \\ & = & 196 \end{align} $$

share|improve this answer
add comment

No you can't distribute the powers like what you did.

There is a theorem called the binomial theorem that controls this type of operations.

The result is clearly $196$. Here is one way to get this result (steps are simplified so that you can follow)

You can do this to simplify the expression:

$$x=(3\cdot4+2)^2$$

then

$$x=(12+2)(12+2)$$

$$x=(12\cdot12)+2\cdot(12\cdot2)+(2\cdot2)$$

$$x=144+48+4 = 196$$

An expression like:

$$x=(a+b)^2$$

can be written as:

$$x=(a+b)(a+b)=a\cdot a+2\cdot a\cdot b+a\cdot a = a^2+2ab+b^2$$

share|improve this answer
add comment

No, you can't distribute the power on any operator, power is distributed on $\times$ and $\div$ not on $+$ and $-$

share|improve this answer
add comment

Can you simplify $$(3\times4 + 2)?$$

then$$(3\times4 + 2)^2$$

by definition $a^2 = a\times a$
let a=$(3\times4 + 2)$

$$ = (3\times4 + 2)\times(3\times4 + 2)$$ multiplication before addition within the parentheses
$$ =(12 + 2) \times(12 + 2)$$ $$ =(14)\times(14)$$ $$= 196$$

The distributive property of multiplication applies to coefficients not to exponents.

a(b+c) = ab+ac

If the 2 was in front as a coefficient then you could write:

$2(3\times 4 +2)$

$= 2\times3\times 4 +2\times 2$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.